Study on the Combustion Behavior of Inhomogeneous Partially Premixed Mixtures in Confined Space - Yanfei Li; Xin Zhang; Lichao Chen; Ying Liu (Energies)
Reasonably configuring the concentration distribution of the mixture to achieve partially premixed combustion has been proven to be an effective method for improving energy utilization efficiency. However, due to the significant influence of concentration non-uniformity and flow field disturbances, the combustion behavior and mechanisms of partially premixed combustion have not been fully understood or systematically analyzed. In this study, the partially premixed combustion characteristics of methane–hydrogen–air mixtures in a confined space were investigated, focusing on the combustion behavior and key parameter variation patterns under different equivalence ratios (0.5, 0.7, 0.9) and hydrogen contents (10%, 20%, 30%, 40%). The global equivalence ratio and degree of partial premixing of the mixture were controlled by adjusting the fuel injection pulse width and ignition timing, thereby regulating the concentration field and flow field distribution within the combustion chamber. The constant-pressure method was used to calculate the burning velocity. Results show that as the mixture formation time decreases, the degree of partial premixing increases, accelerating the heat release process, increasing burning velocity, and shortening the combustion duration. It exhibits rapid combustion characteristics, particularly during the initial combustion phase, where flame propagation speed and heat release rate increase significantly. The burning velocity demonstrates a distinct single-peak profile, with the peak burning velocity increasing and its occurrence advancing as the degree of partial premixing increases. Additionally, hydrogen’s preferential diffusion effect is enhanced with increasing mixture partial premixing, making the combustion process more efficient and concentrated. This effect is particularly pronounced under low-equivalence-ratio (lean burn) conditions, where the combustion reaction rate improves more significantly, leading to greater combustion stability. The peak of the partially premixed burning velocity occurs almost simultaneously with the peak of the second-order derivative of the combustion pressure. This phenomenon highlights the strong correlation between the combustion reaction rate and the dynamic variations in pressure.